Penilaian Kualitas Hidup Terkait Kesehatan Pasien Kanker Payudara di RSUP dr. M. Djamil Padang, Indonesia - Dian Ayu Juwita; Almahdy Almahdy; Rizka Afdila (JURNAL ILMU KEFARMASIAN INDONESIA, 2019)
Health related quality of life is a feeling of comfort and patient satisfaction with the function of controlling diseases including psychological, social, and physical health. Measurement of quality of life needs to be done because therapeutic interventions such as drugs potentialy to increase or decrease the quality of life. The purpose of this study to determine the effect of chemotherapy on the quality of life of breast cancer patients in Dr. M. Djamil Hospital Padang. Assessment of the quality of life of breast cancer patients was performed using an EORTC QLC-30 questionnaire. The sample of the study was breast cancer patients in surgical polyclinic of Dr. M. Djamil Hospital Padang during the period of March to May 2018 meeting the inclusion criteria. The data is rated in the range 0-100 using a linear transformation formula, then presented as a mean value. The quality of life of breast cancer patients based on the functional scale group of cognitive function domain (71,09 ± 21,05), role function (66,65 ± 26,52), physical function (61,97 ± 22,22), emotional function 60,91 ± 18,24), and social function (51,47 ± 15,24), whereas in symptom scale group from diarrhea domain (24,41 ± 23,69), constipation (26,38 ± 29,36) , dyspnea (31.35 ± 31.80), insomnia (42.24 ± 34.26), financial difficulties (48.03 ± 22.24), decreased appetite (53.00 ± 26.28), pain ( 55,41 ± 20,11), fatigue (58,59 ± 17,58), and nausea and vomiting (68,00 ± 28,82), last for general health status / QoL obtained 65,03 ± 14,83.